Chromatin Regulation by HP1γ Contributes to Survival of 5-Azacytidine-Resistant Cells - Imanishi, Satoshi; Umezu, Tomohiro; Kobayashi, Chiaki; Ohta, Tomohiko; Ohyashiki, Kazuma; Ohyashiki, Junko H. (Frontiers in Pharmacology, 2018)
Recent investigations of the treatment for hematologic neoplasms have focused on targeting epigenetic regulators. The DNA methyltransferase inhibitor 5-azacytidine (AZA) has produced good results in the treatment of patients with myelodysplastic syndromes. The mechanism underlying its pharmacological activity involves many cellular processes including histone modifications, but chromatin regulation in AZA-resistant cells is still largely unknown. Therefore, we compared human leukemia cells with AZA resistance and their AZA-sensitive counterparts with regard to the response of histone modifications and their readers to AZA treatment to identify novel molecular target(s) in hematologic neoplasms with AZA resistance. We observed an a decrease of HP1γ, a methylated lysine 9 of histone H3-specific reader protein, in AZA-sensitive cells after treatment, whereas AZA treatment did not affect HP1 family proteins in AZA-resistant cells. The expression of shRNA targeting HP1γ reduced viability and induced apoptosis specifically in AZA-resistant cells, which accompanied with down-regulation of ATM/BRCA1 signaling, indicating that chromatin regulation by HP1γ plays a key role in the survival of AZA-resistant cells. In addition, the amount of HP1γ protein in AZA-sensitive and AZA-resistant cells was decreased after treatment with the bromodomain inhibitor I-BET151 at a dose that inhibited the growth of AZA-resistant cells more strongly than that of AZA-sensitive cells. Our findings demonstrate that treatment with AZA, which affects an epigenetic reader protein and targets HP1γ, or a bromodomain inhibitor is a novel strategy that can be used to treat patients with hematopoietic neoplasms with AZA resistance.